Optimization of multi-residue method for targeted screening and quantitation of 243 pesticide residues in cardamom (Elettaria cardamomum) by gas chromatography tandem mass spectrometry (GC-MS/MS) analysis. (February 2018) - Ahammed Shabeer, T.P.; Girame, Rushali; Utture, Sagar; Oulkar, Dasharath; Banerjee, Kaushik; Ajay, D.; Arimboor, Ranjith; Menon, K.R.K.
Abstract: Higher matrix interference makes the multi-residue pesticide analysis in spices more challenging. A simple, sensitive, and robust large-scale multi-residue method was developed for the rapid analysis of 243 pesticides in cardamom matrix by gas chromatography tandem mass spectrometry (GC-MS/MS). Prehydration of cardamom in 1:4 sample:water for 30 min improved the homogeneity and extractability. QuEChERS extraction followed by cleanup with 25 mg primary secondary amine, 100 mg C18, and 10 mg graphitized carbon black to 1 ml supernatant was used for sample preparation. Reconstitution of final extract in ethyl acetate reduced matrix co-extract up to 60%. The method was validated according to the SANTE/11, 945/2015 guidelines. The limit of quantification was ≤0.01 mg kg −1, and the recovery was within 70.0–120.0%, with ≤20% RSD for the majority of pesticides. The method was used for screening market samples, and the detected residues were devoid of any risk of acute toxicity related to dietary exposure. Graphical abstract: Image 1 Highlights: A comprehensive multi-residue GC-MS/MS method for 243 pesticides in cardamom is reported for the first time. Solvent exchange into ethyl acetate reduces the matrix co-extractives and improves sensitivity. The method facilitates quantification at 0.01 mg kg −1 for >78% of the target analytes in cardamom matrix. The method was successfully applied to screen market samples.